RETROGRADE RECANALISATION OF CORONARY CHRONIC TOTAL OCCLUSIONS - A. A. Larionov; D. P. Gaponov; M. G. Gorbunov; D. A. Korzh; T. N. Kudba; S. A. Kuznetsov (Креативная хирургия и онкология)
Chronic total occlusion of coronary arteries is a condition that is technically difficult to solve by the x-ray surgical methods of treatment, and that is one of the decisive factors in favor of coronary artery bypass grafting. The article presents the results about 27 retrograde recanalization of chronic coronary occlusions and the analysis of reasons of unsuccessful attempts, the frequency and severity of re-operative complications. Retrograde recanalization of chronic total coronary occlusions turned out to be effective in the condition of minimally invasive tactics of myocardial revascularization in single long occlusion. Good distal direction and class CC1 and CC2 collarile appeared to be the main criteria of successful retrograde recanalization. Retrograde recanalization complications are typical for x-ray surgical methods of diagnostics and treatment, they are easily predicted, and the prevention methods are well known and effective. Thus, retrograde recanalization of chronic total coronary occlusions is an efficient way of treatment in case of careful patients’ selection and it should be added to frequently used antegrade recanalization method. The key factors for development and widespread implementation of this method are integration of x-ray surgical methods of diagnostics and treatment together with visualization methods and fluoroscopy with IVUS.